Eksplorasi Etnomatematika Pada Alame Panyabungan Sebagai Makanan Khas - Lubis, Lisda; S, Suparni (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2024)
Mathematics is a universal science that supports the development of modern technology in various fields of science and encourages the development of human thinking. However, many students find mathematics difficult, and this view is often passed down from one generation to the next. Mathematics learning is often closely related to traditional educational processes, which ignore cultural context. Ethnomathematics exists as an approach that utilizes culture in learning mathematics. This research aims to explore the mathematical concepts contained in the typical food, Alame Padangsidimpuan. This research method uses an ethnographic approach by collecting primary data through observation, interviews and documentation, as well as secondary data through literature review. The research results show that Alame Padangsidimpuan contains mathematical concepts such as counting, elements of units, measurement, angles, comparisons, flat shapes, spatial shapes, and social arithmetic. It is hoped that this research can be a valuable reference in developing mathematics learning materials related to local culture, so that students can be more involved and enthusiastic in learning mathematics.